2016
DOI: 10.11002/kjfp.2016.23.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical components and antioxidant activity of Sparassis crispa mixture fermented by lactic acid bacteria

Abstract: The objective of this study was to investigate the nutritional composition and antioxidant activity of a mixture of rice bran and bodies of Sparassis crispa fermented with lactic acid bacteria (LAB). LAB-fermented S. crispa mixture had higher water, crude lipid and crude ash content than that of S. crispa. Insoluble dietary fiber contents of the dried powder of S. crispa and LAB-fermented S. crispa mixture were 46.13% and 33.46%, respectively. β-glucan was higher in dried S. crispa (38.03%) than in LAB-ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…After reviewing these 270 full-text articles on the efficiency of S. crispa extracts for human-disease treatment, thirty-three articles were considered eligible and, therefore, included in the quantitative meta-analysis. One of those articles was written in Japanese [ 21 ], seven in Korean [ 19 , 22 , 23 , 24 , 25 , 26 , 27 ], and the remaining in English. Among them, some studies demonstrated more than two healing effects of the mushroom [ 7 , 26 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing these 270 full-text articles on the efficiency of S. crispa extracts for human-disease treatment, thirty-three articles were considered eligible and, therefore, included in the quantitative meta-analysis. One of those articles was written in Japanese [ 21 ], seven in Korean [ 19 , 22 , 23 , 24 , 25 , 26 , 27 ], and the remaining in English. Among them, some studies demonstrated more than two healing effects of the mushroom [ 7 , 26 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, some studies demonstrated more than two healing effects of the mushroom [ 7 , 26 , 28 , 29 , 30 ]. Simultaneously, the anti-diabetic, anti-tumor, anti-inflammatory, anti-fungal, and antioxidant activities of S. crispa were reported in seven [ 6 , 12 , 14 , 28 , 29 , 30 , 31 ], nine-teen [ 7 , 13 , 15 , 21 , 23 , 24 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], four [ 7 , 22 , 30 , 42 ], three [ 19 , 29 , 43 ], and six [ 8 , 25 , 26 , 27 , 44 , 45 ] studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation